Answer:
The functions are defined as:
- f(3) = -6
- f(0) = 3
- f(1) = 0
Explanation:
We are given a function:
![\bullet \ \ \ f(x) = -3x + 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/h2qfx9eq8zhfz73cirgmitvdur6c3mzhfc.png)
We need to find the values of the function at:
When we replace the x in f(x) with a number, we are saying that "f of 3" or "f of 0" or "f of 1." This means that when we change the x in f(x), we need to also change the rest of the x-variables in the function.
Therefore, to solve f(3), every x must be changed to 3.
![f(x) = -3x + 3\\\\f(3) = -3(3) + 3\\\\f(3) = -9 + 3\\\\f(3) = -6](https://img.qammunity.org/2021/formulas/mathematics/high-school/2k8nrdqhvz3la87md5h9wmq3pzrysvlkdr.png)
We can follow the same method for f(0) and f(1).
![f(x) = -3x + 3\\\\f(0) = -3(0) + 3\\\\f(0) = 0 + 3\\\\f(0) = 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/qwxb23m7w6e005kqces468ts5viogsiadm.png)
And finally, we can solve for f(1).
![f(x) = -3x + 3\\\\f(1) = -3(1) + 3\\\\f(1) = -3 + 3\\\\f(1) = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/68o89krxe67d6qqbyrdey21nunyoau3pkv.png)
Therefore, the function is defined at each value as:
- f(3) = -6
- f(0) = 3
- f(1) = 0